Pemberdayaan Kelompok Perempuan Penenun Dalam Pengembangan Ekonomi Lokal Dan Pelastarian Budaya - Yonas Ferdinand Riwu; Markus Bunga; Dominikus K.T Aman; Yoan Tania Sinlae; Rini Aryani Djo (El-Khidmat, 2025)
Sabu weaving has its own attraction and has become an economic source for the Sabu community, especially women weavers. This service aims to empower women weavers so that they are able to adapt to the changing times, increase income and understanding in digital-based marketing, and maintain the preservation of Sabu weaving culture. The direct education and public assistance method involves involving the "Winirai" Weaver Women's Group which totals 16 people. The result of this service activity is the improvement of skills, the use of technology and marketing strategies through social media with the storytelling method with the strengthening of the narrative about the culture of Sabu Raijua weaving. In addition, this PKM realizes the preservation of the culture and heritage of Sabu weaving in increasing awareness of cultural values and weaving traditions among the younger generation.